2012
DOI: 10.3109/01902148.2011.649823
|View full text |Cite
|
Sign up to set email alerts
|

Apocynin reduces reactive oxygen species concentrations in exhaled breath condensate in asthmatics

Abstract: Asthma is an inflammatory airway disease, and oxidative stress was proven to be involved in its pathogenesis. Apocynin effectively inhibits the main source of reactive oxygen species (ROS)-nicotinamide adenine dinucleotide phosphate (NADPH) oxidase-by blocking its activation. The aim of this study was to investigate the effect of inhaled apocynin on ROS and RNS (reactive nitrogen species) concentration in 14 nonsmoking mild asthmatics. Effects of nebulized apocynin (0.5 mg/mL) were assessed in exhaled breath c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 54 publications
2
43
0
Order By: Relevance
“…Consistent with the involvement of NOX2, inhaled corticosteroids that relieve symptoms also diminished NOX2 mRNA expression in circulating leukocytes from asthmatics. Administration of the NOX2 inhibitor apocynin to asthmatic patients led to decreased H 2 O 2 levels in exhaled breath condensates (284). In guinea pigs, ebselen, a potent NOX2 inhibitor (276,338), was able to improve the ovalbumin-induced asthmatic inflammatory responses, consistent with a role for NOX2 (276,338).…”
Section: Nox2 As a Target For Drug Developmentmentioning
confidence: 68%
See 1 more Smart Citation
“…Consistent with the involvement of NOX2, inhaled corticosteroids that relieve symptoms also diminished NOX2 mRNA expression in circulating leukocytes from asthmatics. Administration of the NOX2 inhibitor apocynin to asthmatic patients led to decreased H 2 O 2 levels in exhaled breath condensates (284). In guinea pigs, ebselen, a potent NOX2 inhibitor (276,338), was able to improve the ovalbumin-induced asthmatic inflammatory responses, consistent with a role for NOX2 (276,338).…”
Section: Nox2 As a Target For Drug Developmentmentioning
confidence: 68%
“…In a model of strokeprone spontaneously hypertensive rats, apocynin significantly decreased the occurrence of stroke (332). In addition, apocynin has been investigated in a Phase 2 human clinical trial for asthma (284), where it showed anti-inflammatory properties, including a decrease in H 2 O 2 in exhaled breath condensates. Thus, while apocynin shows promise as an anti-inflammatory molecule, it remains unclear as to whether its primary mode of action in vivo involves the inhibition of NOX2, its antioxidant properties, or both.…”
Section: Small-molecule Nox Inhibitors: Progress and Prospectsmentioning
confidence: 99%
“…We and others have shown that these markers are useful for noninvasive monitoring to the extent of oxidative stress in the airways. We have also shown that apocynin significantly decreases selected ROS and reactive nitrogen species (RNS) in mild asthmatics (141).…”
Section: Asthmamentioning
confidence: 91%
“…Apocynin treatment in a marmoset model of Parkinson's disease mitigated the disease progression, limiting the parkinsonian signs and motor-function deterioration (Philippens et al, 2013). Moreover, a clinical trial using nebulized apocynin demonstrated a reduction of ROS concentrations in the exhaled breath condensate of asthma patients (Stefanska et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Besides the direct inhibition of neutrophil NADPH oxidase, apocynin prevents the activation of NF-ĸB, which is an important mediator of gastric inflammation (Barnes and Larin, 1997;Lafeber et al, 1999). Apocynin has already been preclinically investigated to tackle inflammatory disorders, such as Parkinson's and Alzheimer's disease, and proved to inhibit airway inflammation in a clinical trial with asthma patients (Lull et al, 2011;Ghosh et al, 2012;Stefanska et al, 2012). This study assessed the anti-inflammatory activity of apocynin in the Mongolian gerbil model for H. pylori-induced gastric disease.…”
Section: Introductionmentioning
confidence: 99%